Media Sosial dan Transformasi Komunikasi Keluarga Muslim - Hamidah, Lilik; Nikmah Hadiati Salisah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2024)
This study examines the role of social media in the transformation of Muslim family communication during the COVID-19 pandemic and the new normal era in the cities of Surabaya, Sidoarjo, and Malang. Using a descriptive qualitative method, the findings of this study reveal that family communication during the pandemic and the new normal era underwent transformations in the types of consensual, pluralistic, protective, and laissez-faire communication, influenced by the conditions and social backgrounds of the informants. Additionally, the role of social media in transforming family communication is quite diverse, depending on the context of each family’s situation. Social media serves functions such as correlation, building networks with external family communities, strengthening support and motivation, and minimizing uncertainty. It also acts as a means of finding and producing entertainment, as well as acquiring new knowledge. From the perspective of uses and gratifications, this study highlights that audiences not only consume media but also produce media content. For children, social media not only functions to build social networking communities within existing circles but also facilitates the formation of new communities based on shared interests.